KECAK DANCE LEARNING AND CULTIVATION OF CHARACTER EDUCATION VALUES IN PASRAMAN WIDYA SANTHI, SEBATU VILLAGE, BALI - Ayana, I Wayan Deo; Arshiniwati, Ni Made; Mawan, I Gede; Karja, I Wayan (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Pasraman, ashram, padukuhan, or gurukula is a traditional education system in Hinduism that has existed since ancient times. Hinduism recognizes that education is an important aspect of human life. In Bali, the history of pasraman has been known since ancient times. In various folktales, there are many touches of education and the existence of padukuhan or pasraman, where Balinese generations gained knowledge in ancient times. This research aims to evaluate Kecak Dance learning in non-formal education in Pasraman Widya Santhi Sebatu Village and to know the process of instilling character education values through Kecak Dance learning in Pasraman Widya Santhi Sebatu Village. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The findings indicate that the learning of the Kecak Dance at Pasraman Widya Santhi is effective through interactive and participatory teaching methods. This learning process not only enhances students' dance skills but also provides a deep understanding of Balinese cultural values. Moreover, the activities successfully instill character education values such as discipline, responsibility, hard work, creativity, and pride in local culture. Community support, a conducive learning environment, and the integration of arts and cultural education are key factors in the program’s success. This study concludes that the learning of the Kecak Dance at Pasraman Widya Santhi serves as an effective model of non-formal education in shaping skilled, character-driven, and culturally aware youth. The structured and culture-based learning process enriches students' artistic skills while fostering awareness of the importance of preserving Bali's cultural heritage